2017
DOI: 10.1002/jbmr.3081
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Treatment With Teriparatide in Patients With Atypical Femur Fractures Previously Treated With Bisphosphonates

Abstract: If oversuppression of bone turnover explained the association between bisphosphonate use and atypical subtrochanteric femur fractures (AFF), this could be reversed with anabolic treatment such as teriparatide. We conducted a prospective, open-label study in patients previously treated with bisphosphonates who sustained AFF, examining the response to 24-month treatment with teriparatide on bone mineral density (BMD), trabecular bone score (TBS), bone turnover markers (BTM), and fracture healing as well as quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…In a recent study by Watts et al [20] whose results were consistent with ours, 14 patients with AFF previously treated with bisphosphonates were followed on teriparatide treatment for 24 months. These patients had fractured 52–410 days prior to beginning teriparatide therapy, and five were incomplete fractures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a recent study by Watts et al [20] whose results were consistent with ours, 14 patients with AFF previously treated with bisphosphonates were followed on teriparatide treatment for 24 months. These patients had fractured 52–410 days prior to beginning teriparatide therapy, and five were incomplete fractures.…”
Section: Discussionsupporting
confidence: 88%
“…Although previous observational studies have often been retrospective, and some have been based on database classification of an AFF, our study was designed to include AFFs that satisfied the majority of the ASBMR classification criteria. In the investigation by Watts et al, they reported that only three of 14 patients demonstrated healing at 12 months, but the definitions of healing were not provided [20]. However, at 24 months, seven of 14 had healed.…”
Section: Discussionmentioning
confidence: 99%
“…A gradual decrease in bone mass has been noted after discontinuation of teriparatide therapy; however, immediate follow-up therapy (consolidation therapy) with a bisphosphonate has been shown to preserve the benefits [92]. Interestingly, variable positive responses (increased bone turnover markers and BMD) to treatment with teriparatide have been reported in patients with atypical femur fractures previously treated with bisphosphonates, but teriparatide should not be relied on to aid in healing of the atypical femur fractures since no consistent effect on fracture healing was observed [93].…”
Section: Anabolic Drugs For the Treatment Of Op Teriparatidementioning
confidence: 93%
“…Since that time, there have been some investigations of bone turnover by histomorphometry and serum markers. In a very recent study [11], patients meeting the updated ASBMR definition of AFF were recruited for an open label study of teriparatide treatment. At baseline, only 1 of 14 subjects had a serum C-telopeptide (CTX) below the reference range, although 5 had levels of bone specific alkaline phosphatase below the normal range.…”
Section: Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
“…Thus, there is obvious heterogeneity in bone histomorphometry, but we cannot conclude that severe suppression of bone turnover is a constant finding in patients with AFF. In another recent study [11] bone was obtained adjacent to the fracture site in women undergoing surgical repair. Using nanoindentation and vibrational spectroscopy, the authors showed that bone was harder and more mineralized in women with atypical fractures after [14], was enough to prevent healing of the crack.…”
Section: Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%